Bimbingan Lanjutan dalam Pertumbuhan Gereja pada Masa Kini - Bert Haniko (Sekolah Tinggi Agama Kristen Lentera Bangsa Manado, 2023)
Abstract: The problems of the church today must be carefully considered in order to think carefully about what must be done to achieve a church growth in accordance with God's will. In fact today the church is not growing because so many people were lost after they accepted Jesus. A general description of continued guidance that results in church growth that is happening today is that the problem is the existence of a weakness and negligence of the church, namely the lack of steady implementation of further guidance services which results in church growth being less stable in quality. Key words: A Church gwoth in accordance with God’s will.